Entrepreneurs' Perception Toward International Cooperation and Government Programs Concerning Entrepreneurship - Saucedo-Bendek, Omaira; Ewel, Sebastián; Roman-Roig, Francisco Javier (Frontiers in Education, 2020)
Entrepreneurs’ Perception Towards International Cooperation and Government Programs Concerning Entrepreneurship